The relationship between personal responsibility and pro-environmental intention in high schools' students - Dasi, Ahsanul Akhsan; Miarsyah, Mieke; Rusdi, Rusdi (Jurnal Pendidikan Biologi Indonesia, 2019)
The role of personal responsibility is important to foster a pro-environmental intention can change students' pro-environmental behavior. This study aims to analyze the relationship between personal responsibility and pro-environmental intention in XI-MIPA students at SSHS of 8 Makassar, South Sulawesi. This study used a quantitative approach with a descriptive method of correlation techniques. Partisipants for study were 120 students. Data collection used non-test instruments. Analysis of research data used a regression model test (α = 0.05) and coefficient test with Pearson Product Moment test (α = 0.05). The results showed that there was a positive relationship between personal responsibility and pro-environmental intention. Students who have a high personal responsibility have several advantages, namely (1) can learned how to respect the rights and feelings of others, decide their own desires and the importance of being responsible; (2) able to become independent learners, able to play an active role in learning  and their desires more responsibly, and (3) can learn how to respect the rights and feelings of others, decide their own desires and the importance of being responsible.